1994
DOI: 10.1111/j.1476-5381.1994.tb13214.x
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism by lipophilic quaternary ions of the K+ channel opener, levcromakalim, in vascular smooth muscle

Abstract: 1 The aim of this study was to characterize the interaction between the K+ channel opener levcromakalim (LKM) and several quaternary ions, in vascular smooth muscle, in vitro. Segments of isolated, thoracic aorta of the rat were suspended in organ baths filled with Krebs solution at 37C. Cumulative concentration-response curves to LKM were obtained in the absence and in the presence of increasing concentrations of quaternary ions using a number of agents to pre-constrict the vessel. The ions tested were tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…At this time it is uncertain where lipophilic quaternary ions interact with the K ATP channel. However, previous studies with other quaternary ions have suggested that they interact with the pore of the K + channel to inhibit K + efflux from the cell (see McPherson and Piekarska 1994). The potency and nature of the antagonism displayed by the imidazolines characterised in this study are similar to that displayed by the lipophilic quaternary ions.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…At this time it is uncertain where lipophilic quaternary ions interact with the K ATP channel. However, previous studies with other quaternary ions have suggested that they interact with the pore of the K + channel to inhibit K + efflux from the cell (see McPherson and Piekarska 1994). The potency and nature of the antagonism displayed by the imidazolines characterised in this study are similar to that displayed by the lipophilic quaternary ions.…”
Section: Discussionsupporting
confidence: 59%
“…Another potent group of levcromakalim antagonists that have been identified are the lipophilic quaternary ions such as tetraphenylphosphonium (pK B =7.2; McPherson and Piekarska 1994;Piekarska and McPherson 1997). While displaying the same potency as glibenclamide, tetraphenylphosphonium (and related compounds) show a markedly different type of antagonism as that displayed by the sulphonylureas.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus when using sulphonylurea based compounds the levcromakalim concentration‐effect curve is shifted to the right in a parallel manner with no obvious effect on the maximum response. Another potent group of levcromakalim antagonists that we have identified are the lipophilic quaternary ions such as tetraphenylphosphonium (pK B =7.2; McPherson & Piekarska, 1994; Piekarska & McPherson, 1997). While displaying the same potency as glibenclamide, tetraphenylphosphonium (and related compounds) show a markedly different type of antagonism as that displayed by the sulphonylureas.…”
Section: Discussionmentioning
confidence: 99%
“…TPA + constricts the rat mesenteric artery at low concentrations (5-10 µM), but acts as a non-selective relaxant in rat arteries at concentrations above 10 µM, whereby this effect is not associated with its blocking effect on vascular K + channels (Huang 1997). Two other lipophilic quaternary compounds, tetraphenylphosphonium and tetraphenylarsonium, are among the most potent antagonists of levcromakalim-mediated vasorelaxation (McPherson and Piekarska 1994). Some quaternary ions are highly lipophilic, which allows them to cross the hydrophobic core of the plasma membrane to interact with K + channels or other intracellular molecules.…”
Section: Introductionmentioning
confidence: 98%